2015
DOI: 10.3168/jds.2014-8732
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genetic parameters for fertility in dairy cows from in-line milk progesterone profiles

Abstract: The aim of this study was to define endocrine fertility traits from in-line milk progesterone (P4) records and to estimate genetic parameters for these traits. Correlations of classical fertility (calving interval and calving to first service) and milk production traits with endocrine fertility traits were also estimated. In-line milk P4 records (n=160,952) collected from June 2009 through November 2013 for 2,273 lactations of 1,561 Holstein-Friesian cows in 12 commercial herds in the Netherlands were analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
42
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(60 citation statements)
references
References 26 publications
(56 reference statements)
14
42
4
Order By: Relevance
“…The luteal phase length (mean ± SD) preceding AI was 13.7 ± 6.2 d, similar to previous reports of 12.9 ± 5.0 (Lamming and Darwash, 1998) and 13.0 ± 11.5 d (Tenghe et al, 2015). The inter-luteal phase length averaged 12.0 ± 3.7 d and was greater than the 7.8 ± 4.3 and 9.3 ± 8.5 d reported by Lamming and Darwash (1998) and Tenghe et al (2015), respectively. Repeat-ability estimates for luteal and inter-luteal lengths were 0.16 and 0.09, respectively, which were greater than that of Tenghe et al (2015), who reported estimates close to zero for both variables.…”
Section: Characterization Of In-line Milk Progesterone Profilessupporting
confidence: 86%
See 4 more Smart Citations
“…The luteal phase length (mean ± SD) preceding AI was 13.7 ± 6.2 d, similar to previous reports of 12.9 ± 5.0 (Lamming and Darwash, 1998) and 13.0 ± 11.5 d (Tenghe et al, 2015). The inter-luteal phase length averaged 12.0 ± 3.7 d and was greater than the 7.8 ± 4.3 and 9.3 ± 8.5 d reported by Lamming and Darwash (1998) and Tenghe et al (2015), respectively. Repeat-ability estimates for luteal and inter-luteal lengths were 0.16 and 0.09, respectively, which were greater than that of Tenghe et al (2015), who reported estimates close to zero for both variables.…”
Section: Characterization Of In-line Milk Progesterone Profilessupporting
confidence: 86%
“…The inter-luteal phase length averaged 12.0 ± 3.7 d and was greater than the 7.8 ± 4.3 and 9.3 ± 8.5 d reported by Lamming and Darwash (1998) and Tenghe et al (2015), respectively. Repeat-ability estimates for luteal and inter-luteal lengths were 0.16 and 0.09, respectively, which were greater than that of Tenghe et al (2015), who reported estimates close to zero for both variables. The variation in inter- Variables were categorized based on quartiles and receiver operating characteristic (ROC) curve analysis cut-points (below vs. above).…”
Section: Characterization Of In-line Milk Progesterone Profilescontrasting
confidence: 54%
See 3 more Smart Citations